Clean fixation of dye on cotton in supercritical carbon dioxide with a heterogeneous and phase transfer catalytic reaction. (April 2015) - Long, Jia-Jie; Cui, Chuang-Long; Zhang, Yan-Qin; Yuan, Guo-Hao
Abstract: A clean fixation of disperse reactive dye on cotton was investigated by employing a heterogeneous and phase transfer catalytical reaction with a phase transfer agent in a liquid-supercritical-solid triphase system, as an environmentally friendly alternative to conventional and heavy pollutional wet-chemical process. The catalytic fixation reaction was characterized by color intensity, fixation efficiency and Fourier transform infrared spectrometry (FT-IR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM). The results show that the dye fixation through a nucleophilic addition at a solid cellulosic polymer substrate phase could be effectively facilitated as the transportation of the anion of OH − or CO3 2− by the phase transfer catalyst of FC-134 from a liquid phase to supercritical phase and then onto the solid substrate in a self-built reactor. A heterogeneous and triphase transfer catalytic reaction mechanism was also supposed for the dye fixation at the solid substrate in supercritical carbon dioxide fluid with the presence of a base. Graphical abstract: Highlights: Basic information for dye fixation was explored on cotton with phase-transfer catalyst. Significant improvement of dye fixation efficiency and color strength was achieved. The catalytic fixation reaction was characterized and confirmed by FT-IR, XPS, SEM. Dye fixation could be effectively facilitated by phase transfer catalyst of FC-134.